HUBUNGAN HUKUM DALAM PERJANJIAN PEMBORONGAN - Hanafi Darwis (Faculty of Law, Universitas Diponegoro, 2012)
Agreement (Overeenkomst) is an event when one party promises to another party to perform a case based on the event, and then the legal relations arise between both parties. In the Contracting Agreement, the Principles of Legal Relations between both parties explained on (Burgerlijk wetboek) certain following principles: Principle of responsibilities correlations of all parties, Principle of the assertiveness of contractor responsibilities, Principle of the prohibition to any changes in the agreement price, Principle of the freedom to terminate the agreement unilaterally.Key Words: Legal Relations, Contracting Agreement